Study on Catastrophe Theory of Activation-Induced Prominence of Faults under Dynamic Disturbance. (29th October 2018) - Zuo, Yujun; Wang, Hao; Yu, Meilu; Dou, Xiaoxiao; Wu, Zhonghu; Wang, Jian
Abstract : In view of the phenomena of coal and gas outburst induced by fault activation under dynamic disturbance, a mechanical model of faults and surrounding rock mechanics was established based on the theory of fold catastrophe. Moreover, the dynamic disturbance factors were introduced and analyzed to analyze the influencing factors of outburst coal rock outburst. Through theoretical analysis, it shows that the thinner the fault medium is, the more energy the external input is required for system instability, and the external energy can reflect the stability of the system. When the width of fault media is fixed, the stronger the mining disturbance, the less energy the external input is required for system instability; on the contrary, the weaker the mining disturbance is, the more energy the external input is required for system instability. In addition, through the equation of conservation of kinetic energy, it can be seen that the stronger the mining disturbance, the greater the critical value of the surrounding rock thickness. The paper introduces the dynamic disturbance parameters through the catastrophe theory and analyzes the influence of the existence of faults on coal and gas outburst in detail, which provides a new theoretical basis for the prediction and prevention of coal and gas outburst disasters.